2003
DOI: 10.1007/s10228-003-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition and phylogenetic relationships of the family Pinguipedidae (Teleostei: Perciformes)

Abstract: The phylogenetic relationships of the family Pinguipedidae plus the genus Cheimarrichthys von Haast, 1874, were studied to redefine the family. Based on a phylogenetic analysis using derived characters belonging to 21 transformation series, accepting the monophyly of Pinguipedidae plus Cheimarrichthys provisionally for the operational procedure of the analysis, it was hypothesized that Cheimarrichthys is not closely related to Parapercis Bleeker, 1863, although these genera had been considered as having a clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…We first described histological transformations of gonads during sex change. Similar to a previous study in the focal species (Hasebe, 2019), we found that male germ cells were present in all observed gonads, and no individuals without testicular components were present, suggesting that females form ovotestes in this species.…”
Section: Gonadal Changes During Sex Changesupporting
confidence: 90%
See 4 more Smart Citations
“…We first described histological transformations of gonads during sex change. Similar to a previous study in the focal species (Hasebe, 2019), we found that male germ cells were present in all observed gonads, and no individuals without testicular components were present, suggesting that females form ovotestes in this species.…”
Section: Gonadal Changes During Sex Changesupporting
confidence: 90%
“…Our study, together with a previous study (Hasebe, 2019), revealed geographic differences in the threshold of body length at which sex change initiates. Body size (LT and LS) successively increased in association with the progression of sex change (Figure 3a,b).…”
Section: Body Length and Gsi Distributions And Thresholds Of The Sex ...supporting
confidence: 77%
See 3 more Smart Citations